Digital guerrilla marketing: An innovative method of utilizing online communication channels to connect with the target audience - Baltezarević Radoslav; Baltezarević Ivana (Megatrend Revija, 2024)
Guerrilla marketing provides a novel and economical approach to audience engagement through surprise and inventiveness. This marketing strategy uses cognitive and emotional cues to provide unforgettable experiences that appeal to customers. In order to turn audiences from passive recipients of a brand's message into active participants in its story, guerrilla marketing uses the power of surprise, delight, and intrigue. Both online and offline, guerrilla marketing is distinguished by its creative and captivating strategies, which are modeled after the effective and resourceful methods of traditional guerrilla marketing. With the rise of social media and the internet, guerrilla marketing has evolved. To reach a larger audience, it now employs a range of digital tactics, but the core principles remain the same: creativity, resourcefulness, and a limited budget. Nevertheless, the arsenal of tools has expanded. Companies can leverage data, content, real-time engagement, social media analytics, agility, and user-generated material to create innovative and successful guerrilla marketing strategies that engage their target audience in the always-evolving digital landscape. Digital guerrilla marketing is not the same as regular online platform usage. Rather than the physical, frequently public pranks of classic guerrilla marketing, it emphasizes viral content, social media interaction, and digital campaigns. Guerrilla campaigns aim to be creative in order to stand out in the crowded digital space by drawing in viewers with original and inventive content.